2020 IEEE International Ultrasonics Symposium (IUS) 2020
DOI: 10.1109/ius46767.2020.9251841
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Transducers for High Pressure Environments Up to 1000 Bar

Abstract: This paper studies the influence of high ambient pressure on ultrasound transducers where the piezoelectric layer is bonded to the acoustic matching layer by two different methods: Au-Sn solid-liquid interdiffusion and standard polymer adhesives. The transducers were fabricated by bonding 6 MHz piezoelectric elements to silicon matching layers. Electrical impedance was measured on the transducers during exposure to 1000 bar pressure at 15 °C in a silicone oil filled pressure vessel. The bondlines of the transd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…There is industrial need and academic interest in engineering ultrasound transducers for environments of elevated pressure. For example, a recent study has demonstrated the operation of 6 MHz piezoelectric composites bonded to matching layers towards at 1000 bar in silicone oil [28], though this study along with others, do not consider a configuration like the FUT.…”
Section: Novel Contributions To Knowledgementioning
confidence: 95%
“…There is industrial need and academic interest in engineering ultrasound transducers for environments of elevated pressure. For example, a recent study has demonstrated the operation of 6 MHz piezoelectric composites bonded to matching layers towards at 1000 bar in silicone oil [28], though this study along with others, do not consider a configuration like the FUT.…”
Section: Novel Contributions To Knowledgementioning
confidence: 95%